Effect of the Al Doping on the Sensing Behaviour of Carbon Nanotubes Toward Carbazochrome: a Computational Study - GENÇ, Fatma; KANDEMİRLİ, Fatma (Afyon Kocatepe Universitesi Fen Ve Muhendislik Bilimleri Dergisi, 2022)
In the current report, the interaction of Al-doped carbon nanotubes (CNT) with carbazochrome, an anti-hemorrhagic or hemostatic agent, was investigated with the M06-2X functional and 6-31G* basis set. The global index including frontier molecular orbital energies, hardness, softness, chemical Gibbs energies and some parameters and NLO properties of Carbazochrome, Al doped CNT and complexes formed between their were calculated and evaluated. Electron localization function (ELF) calculations were performed to validate the essence of the formed bonding model progress along the interaction. It is obtained that polarizability of the complex are bigger than those of Carbazochrome and Al doped CNT. According to the maximum electron flow index, the electrophilicity power is increased by increasing the chemical potential, the decreasing chemical hardness. All obtained complexes are exergonic and thus thermodynamically favorable
Keywords: Carbazochrome; Al doped CNT; Electron Localization Function (ELF); Computational Study; Carbazochrome; Electron Localization Function (ELF); Hesaplamalı Çalışma; Elektron Lokalizasyon Fonksiyonu (ELF); Atomic, Molecular and Optical Physics; Al doped CNT; Computational Study; Atomik, Moleküler ve Optik Fizik; Karbazokrom; Karbazokrom; Hesaplamalı Çalışma; Al doped CNT; Elektron Lokalizasyon Fonksiyonu (ELF)